Solve 0 = 4×2 12x 9. select the equation that shows the correct substitution of a, b, and c in the quadratic formula.

Question

Solve 0 = 4×2 12x 9. select the equation that shows the correct substitution of a, b, and c in the quadratic formula.

in progress 0
King 1 month 2022-12-31T08:16:22+00:00 2 Answers 0 views 0

Answers ( 2 )

    0
    2022-12-31T08:17:54+00:00
    Answer:
    Solve 0 = 4×2 + 12x + 9. select the equation that shows the correct substitution of a, b, and c in the quadratic formula.
    We know that quadratic equation for:
    ax^2 + bx + c= 0…………(1) is
    X = {- b + – √( b^2 -4ac) } / 2a ……….(2)
    for calculating the value of x. where a, b and c values are given in numeric.
    So , here if we compare the value of 0 = 4x^2 + 12x + 9 with equation no 1 then we can get
    a = 4 , b= 12 and c = 9
    So from these we can get
    X = {- 12 + – √(12^2 – 4*4*9)} / 2*4
    X = {- 12 + – √(12*12 – 4*4*9) } / 2*4
    X = – 12 + – (√144 – 144) / 2*4
    X = – 12 + 0 /8
    X= – 3/2
    So the implemented equation of 0 = 4x^2 + 12x + 9. Will be X ={ – 12 + – √(12*12 – 4*4*9 )/ 2*4} and the calculated value of x will be -3/2
    Know more about “Quadratic Equation” here: https://brainly.com/question/28317310
    #SPJ4

    0
    2022-12-31T08:18:06+00:00
    We get the value of x as – 3 / 2 and the quadratic equation is represented by a x² + b x + c= 0.
    We know that the formula for quadratic equation is given by:
    a x² + b x + c= 0
    Here, we have the quadratic equation as:
    4x² + 12 x + 9 = 0
    We will solve it by using middle term splitting.
    We can write the equation as:
    4 x² + 6 x + 6 x + 9 = 0
    Taking common factors:
    2 x ( 2 x + 3) + 3 ( 2 x + 3) = 0
    Again taking the common factors:
    (2 x + 3)(2 x + 3) = 0
    Solving it to get the value of x:
    x = – 3 / 2 and – 3 / 2.
    Therefore, we get the value of x as – 3 / 2 and the quadratic equation is represented by a x² + b x + c= 0.
    Learn more about quadratic equation here:
    #SPJ4

Browse

Giải phương trình 1 ẩn: x + 2 - 2(x + 1) = -x . Hỏi x = ? ( )